PENERAPAN STRATEGI COOPERATIVE LEARNING TIPE TTW (THINK TALK WRITE) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - Ratih, Risna; Sudin, Ali; Hanifah, Nurdinah (Jurnal Pena Ilmiah, 2017)
Based on observation of research which conducted on students grade Vb SDN 1 Keraton, Suranenggala Sub-District, Cirebon Regency, 2016/2017  academic year, it can be seen that the activity and student learning outcomes on the subject of economic activity in Indonesia are still below the KKM that has been determined by the school, with 68% percentage. Learning activities students which ineffective,  influenced by the student's lack of discipline while following the lesson and not obeying the rules. The research is using classroom action research (PTK) with research design that refers to Kemmis and Taggart scientists, which consists of planning, action, observation, and reflesi. The instruments used are interviews, field notes, student activity observation format, teacher performance, and student learning outcomes.  from the research that has been done, It can be concluded  that the implementation of cooperative learning strategy, type TTW (Think Talk Write) is able to increase activity and student learning outcomes in the material of economic activity in Indonesia. The evident showing that from defined target, 85% student achieve KKM. On social science learning, 94,12% students avowed complete.